A Trusts Act for New Zealand. Issue 9 (3rd October 2019) - Cone, Geoffrey; Shan, Claudia; Barber, Simon
Abstract: There has been a seismic overhaul of trust law in New Zealand, culminating in the Trustee Act 1956 being replaced by the Trusts Act 2019. The latter reflects modern trust practice and its key features include clarifying the powers, duties, roles and requirements of trust participants, and streamlining various processes. In this article, we focus on a number of these features, with a particular focus on practical insights on the improvements and advantages of New Zealand trust law for domestic as well as international practitioners, settlors, beneficiaries and protectors alike.